Influência do Gene α-actinina 3 na lesão muscular induzida pela maratona internacional de São Paulo em atletas amadores - Maciel, Jaqueline Fernanda de Souza (2019)
The marathon can cause muscle damage, which can be verified by increasing levels of blood biomarkers. There are variations in the genes that can be associated with a greater predisposition to muscular injuries induced by physical exercises. The polymorphism is characterized by a variation in a given DNA sequence in more than 1% of the population. The R577X polymorphism gene ACTN3 influences the distribution of fiber typing, consequently muscle structure and function. Previous studies have investigated the role of this polymorphism in sports performance and muscle function and injury in different types of exercise. We investigated the influence of the α-actinin-3 gene R577X polymorphism on marathon-induced muscle injury in amateur athletes. The study included 81 male amateur marathoners, mean age of 40 ± 1 years, 77 ± 4 kg, body mass index 24.5 ± 06 kg/m2, 7 ± 5 years of experience in long-distance exercise and finishers of the São Paulo International Marathon 2015, time race 261 ± 6 min. Blood samples were collected one day before the marathon, immediately after the marathon, 1, 3 and 15 days after marathon for evaluation of muscle injury markers (creatine kinase, CK, myoglobin, lactate dehydrogenase, DHL, glutamic oxalacetic transaminase, TGO, and pyruvic glutamic transaminase, TGP). Genotyping analysis was performed using the PCR method. The marathon induced an increase in plasma levels of CK (approximately 20-fold), DHL (2-fold), TGO (2.5-fold), TGP (1.4-fold), and myoglobin (20-fold). CK, TGO and DHL activity returned to baseline levels 15 days after the marathon. The activity of TGP and myoglobin concentration remained altered in the RX and XX genotypes after 15 days while returning to the baseline values in the RR genotype. Genotype XX had higher plasma concentration of CK, TGO, TGP, DHL and myoglobin 3 days after marathon when compared to RR genotype. Myoglobin concentration was also higher in XX genotype 1 day after marathon, when compared to the RR genotype. It was not possible to indicate a genotype more susceptible to muscle injury through the biomarkers used, but it was evident the later recovery of muscle injury induced by long-distance exercise in genotype XX compared to RR. The individuality of the athlete as their genetic profile is important for a more effective periodization, reducing the risk of injuries caused by insufficient recovery time.